POWER SITUATION OF HYDROCARBONS IN PERU - Rojas Lazo, Oswaldo (2006)
The rate of annual growth of energy comsumption in the world increases at a rate of 2 to 3%, having hydrocarbons and coal like its main components. In Peru the proven reserves of energy are: gas (Camisea) with 43% of the commercial energy, 23.1% of hydroenergy, natural gas liquids with 14.7% and others with 19,2%. The power trade balance in Peru is negative, petroleum production in the last years this descending whereas gas production and gas liquids are increasing. Camisea is the more important gas project of Peru, the construction of the liquefaction plant will be used for the export and the implementation of basic petrochemical industries. Gas will become important in the change of Peru's power matrix.